Diagnostic implications of associated defects in patients with typical orofacial clefts - Isabella Lopes Monlleó; Amanda G.R. de Barros; Marshall Ítalo Barros Fontes; Ana Karolina Maia de Andrade; Gisèle de Mattos Brito; Diogo Lucas Lima do Nascimento; Vera Lúcia Gil‐da‐Silva‐Lopes (2015)
To describe prevalence of associated defects and clinical-genetic characteristics of patients with typical orofacial clefts seen at a reference genetic service.Descriptive study conducted between September of 2009 and July of 2014. Two experienced dysmorphologists personally collected and coded clinical data using a validated, standard multicenter protocol. Syndromic cases were defined by the presence of four or more minor defects, one or more major defects, or recognition of a specific syndrome. Fisher's exact and Kruskal-Wallis tests were used for statistics.Among 141 subjects, associated defects were found in 133 (93%), and 84 (59.5%) were assigned as syndromic. Cleft palate was statistically associated with a greater number of minor defects (p<0.0012) and syndromic assignment (p<0.001). Syndromic group was associated with low birth weight (p<0.04) and less access to surgical treatment (p<0.002). There was no statistical difference between syndromic and non-syndromic groups regarding gender (p<0.55), maternal age of 35 years and above (p<0.50), alcohol (p<0.50) and tobacco consumption (p<0.11), consanguinity (p<0.59), recurrence (p<0.08), average number of pregnancies (p<0.32), and offspring (p<0.35).There is a lack of information on syndromic clefts. The classification system for phenotype assignment adopted in this study has facilitated recognition of high prevalence of associated defects and syndromic cases. This system may be a useful strategy to gather homogeneous samples, to elect appropriate technologies for etiologic and genotype-phenotype approaches, and to assist with multiprofessional care and genetic counseling.